Pengaruh Work-life Balance dan Kepuasan Kerja terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior (OCB) sebagai Variabel Intervening - Azmi Azizah, Ardhita; Kusumawardani , Mawar Ratih (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work-life balance and job satisfaction on employee performance, with Organizational Citizenship Behavior (OCB) as an intervening variable. The objective is to analyze direct and indirect relationships among these variables. This quantitative study used a survey method involving 49 employees of the Tourism and Culture Office of Kediri Regency. Data were analyzed using multiple regression, path analysis, and the Sobel test. The results show that job satisfaction and OCB significantly improve employee performance, while work-life balance has no significant effect. The findings imply that improving job satisfaction can strengthen OCB and employee performance.